2022
DOI: 10.1002/mp.15650
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality surgical navigation system based on the spatial drift compensation method for glioma resection surgery

Abstract: Background The number of patients who suffer from glioma has been increasing, and this malignancy is a serious threat to human health. The mainstream treatment for glioma is surgical resection; therefore, accurate resection can improve postoperative patient recovery. Purpose Many studies have investigated surgical navigation guided by mixed reality, with good outcomes. However, the limitations of mixed reality, such as spatial drift caused by environmental changes, limit its clinical application. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In 30 studies (38%), the use of a head-mounted device for neurosurgery was evaluated ( Supplemental Digital Content 2, Table 1 , http://links.lww.com/ONS/B48). 10-86 In most of these studies, the HoloLens (Microsoft) was used for AR visualization. In 26 studies (32%), an image overlay, for either the microscopic or endoscopic field of view, was used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 30 studies (38%), the use of a head-mounted device for neurosurgery was evaluated ( Supplemental Digital Content 2, Table 1 , http://links.lww.com/ONS/B48). 10-86 In most of these studies, the HoloLens (Microsoft) was used for AR visualization. In 26 studies (32%), an image overlay, for either the microscopic or endoscopic field of view, was used.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported on multiple evaluation metrics ( Supplemental Digital Content 3, Table 2 , http://links.lww.com/ONS/B49). 10-83,85-90 Based on the results of this review, the following evaluation categories have been defined: (1) registration accuracy, (2) clinical outcome, (3) time measurements, (4) task performance, (5) technical reliability, and (6) user perception (Table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to ARToolkit, Vuforia SDK can Some articles also proposed their own tracking methods using custom-designed markers. An AR-guided neurosurgical navigation system for glioma resection was developed, and the HoloLens recovery accuracy of 0.88 mm was measured by using a marker pose estimation method (Zhou et al 2022). Custom-designed markers were also used by XVision, which was the first FDA-approved AR device for spine surgery, and the initial clinical experience showed good outcomes (Dibble and Molina 2021).…”
Section: Tracking With Integrated Cameramentioning
confidence: 99%
“…Most of the studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ] in this review are focused on application of HoloLens 2 in surgical navigation in the operating room and in the emergency department. The use of the AR/MR based system in this context provided the user with computer-generated information superimposed to real-world environment and improved accuracy, safety and efficacy of surgical procedures [ 86 ].…”
Section: Ms Hololens 2 Applications In Medical and Healthcare Context...mentioning
confidence: 99%